Vacuum drying of cyclohexane from solvent‐extracted oil sands gangue. (1st November 2016) - Renaud, Richard; Pal, Krupal; Weiß, Tobias; Choi, Phillip; Liu, Qi; Gray, Murray R.
Abstract: Solvent‐based extraction has the potential to give higher bitumen recovery from mined oil sands without further accumulation of tailings ponds. A crucial aspect of this technology is the recovery of solvent from the solid waste stream, or gangue. Experiments were performed on gangue after cyclohexane extraction from high‐ and low‐grade oil sand ores to determine the effects of drying temperatures from 25 to 105 °C and pressures from 30 to 95 kPa. Increasing temperature and decreasing pressure both increased the mass flux of evaporating cyclohexane. The maximum mass flux of cyclohexane correlated strongly with cyclohexane vapour pressure at the oven temperature. The total time required to reach a target residual cyclohexane concentration of 250 mg/kg followed a power law relationship with both temperature and pressure, ranging from 300 to 9000 s depending on oven temperature and pressure. Evaporation of solvent was slower from the gangue from low‐grade ore, with a total completion time 3.2 ± 0.9 (n = 33) times longer compared to gangue from high‐grade ore at the same temperature and pressure. The higher water and fines contents of the gangue from low‐grade ore likely contributed to this result.